How to excel in science competitions - Krieger, Melanie Jacobs (New York : F. Watts, 1991)
A guide for the high school student researching a science project for entry in a competition.
Includes bibliographical references (p. 139-140) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Ad.-Adult.
Young Adult
Keywords: High school students -- Competitions; Research -- Competitions; Science projects; Research -- Competitions; Science projects; Research -- Competitions; Science -- Experiments